Stalk-eyed fly, Diopsis sp. population dynamics under varying temperature and Relative Humidity in rice ecosystems - Kayongo, Charles; Mbogga, Michael S.; Goncalves de Abreu, Aluana; Masika, Fred; Masanza, Michael; Freitas Barrigossi, Jose Alexandre; Kizito, Elizabeth B. (My University, 2018)
Although the stalk-eyed fly (Diopsis sp.) has been observed in Ugandan rice fields, there is limited information on the fly’s population and its potential threat to rice production. This study assessed the stalk-eyed fly (Diopsis longicornis and Diopsis apicalis) population dynamics under varying temperature and relative humidity in rice ecosystems of Uganda. It was conducted in purposively selected small scale rice farming sub-counties in low land rain fed and irrigated rice agro-ecologies (Lake Victoria Crescent, Kasese transition zone and Northern moist farmlands). Diopsis sp. populations were monitored by sampling rice fields every 40 days for a period of 17 months. Weather parameters including air temperature and humidity were recorded by use of data loggers throughout the study period. R-statistical tool and MS Excel were used to assess the population dynamics and interactions of the diopsids. D. longicornis fly was dominantly abundant in rice fields of Lake Victoria Crescent and Northern Moist zones while D. apicalis was dominant in Kasese transition zone. There was significant mean count variations per survey for both species in all the agro-ecological zones with P-values of 0.000958 (D. longicornis) and 1.12e-12 (D. apicalis) in Lake Victoria crescent, 0.000473 (D. apicalis) and 0.0173 (D. longicornis) in Northern moist farmlands, 0.0188 (D. apicalis) and 0.0353 (D. longicornis) in Kasese transition zone. Temperature and relative humidity had a direct effect on the population of both species in Northern moist zone and only on D. apicalis in Kasese transition zone. The optimum/favorable temperatures for abundance were between 27oC and 29oC. Interpretation of the results? Integrated pest management strategies and introduction of improved Diopsis pest resistant rice varieties are some of the recommendations for managing the stalk-eyed fly populations in these rice ecosystems.
Keywords: Rice ecosystems; Diopsis longicornis; Diopsis apicalis; Temperature; Agro – ecological zones; Relative Humidity